The taxation of Electronic Commerce in the ecuadorian tax context - Gutiérrez Jaramillo, Néstor Daniel (2020)
Objective: Determine the taxation of electronic commerce in the Ecuadorian tax context. Method: The focus of the study was documentary, exploratory and descriptive in which the information was selected from the critical reading of documents and bibliographic material, official information and statistics from national and international organizations. Results: Although it is evident that e-commerce in Ecuador is growing steadily, with transactions that in 2018 exceeded one billion dollars, in the tax field these types of transactions are very difficult to control, quantify and measure, mainly due to the limitation in terms of tax residence, both for the seller and the buyer, becoming a great obstacle for the tax administration. Conclusions: In Ecuador, there is no tax regulation related to electronic commerce, that is, the Internal Tax Regime Law does not indicate the generating fact that is conceived when carrying out a transaction using electronic means, nor the subject who is obliged to pay taxes for carrying out said activities.